Life Expectancy in Iraq (2000–2022): A Trigger to the Revamp Health System and Public Health Policies - Salman Rawaf; Celine Tabche; David L. Rawaf (مجلة كلية الطب)
Life expectancy at birth is one of the most critical indicators of a population's health, reflecting the cumulative effects of healthcare access, lifestyle, socioeconomic factors, and public health strategies (1). Between 2000 and 2022, life expectancy trends in Iraq were shaped by political instability, conflicts, economic sanctions, and evolving risk factors such as lifestyle-related diseases, environmental hazards, and fragmented health services. This article explores these trends, focuses on statistical data and regional comparisons, and recommends actions to address Iraq’s public health challenges.